2011
DOI: 10.1111/j.1365-2524.2010.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of culturally appropriate interventions to manage or prevent chronic disease in culturally and linguistically diverse communities: a systematic literature review

Abstract: Culturally and linguistically diverse (CALD) communities in Australia experience both significant health disparities and a lack of access to services. Consequently, there have been calls for culturally appropriate services for people with chronic disease in CALD populations. This paper presents a systematic review of the literature on the effectiveness of culturally appropriate interventions to manage or prevent chronic disease in CALD communities. Evidence was sought from randomized controlled trials and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
139
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 40 publications
4
139
0
3
Order By: Relevance
“…[14] These notable disparities in health and health care suggest the need for increased attention to specific cultural differences and how these differences relate to health outcomes. [3][4][5][6] Regardless of the method of implementation (integration of specific theory or model, integrated concepts throughout several courses, stand-alone course on culture), graduates are only achieving cultural awareness.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…[14] These notable disparities in health and health care suggest the need for increased attention to specific cultural differences and how these differences relate to health outcomes. [3][4][5][6] Regardless of the method of implementation (integration of specific theory or model, integrated concepts throughout several courses, stand-alone course on culture), graduates are only achieving cultural awareness.…”
Section: Significancementioning
confidence: 99%
“…[1] In addition to the influence of ethnic diversity, other cultural variables such as varying attitudes, beliefs, and life circumstances affect a person's health status, perspective on health care and their ability to access it. [2][3][4][5][6] The increase in minority populations, as well as the varying beliefs and practices of a highly diverse population, have attributed to the problem of disparities in health and health care. [2] Health disparities refer to the differences in the state of health of a person as it relates to a person's race/ethnicity, socioeconomic status, age, location, gender, disability status, and sexual orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Several features have been identified as critical in development of culturally safe chronic disease management and rehabilitation programs for Aboriginal and Torres Strait Islander people and for culturally and linguistically diverse populations more generally [7] [8]. These include information that is accessible and culturally relevant, adequate aboriginal community engagement, utilising local knowledge, strong leadership, shared responsibilities, sustainable resources and integrated data and systems, and the involvement of Aboriginal and Torres Strait Islander staff in service delivery and the integration of care across conditions and sectors [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…These include information that is accessible and culturally relevant, adequate aboriginal community engagement, utilising local knowledge, strong leadership, shared responsibilities, sustainable resources and integrated data and systems, and the involvement of Aboriginal and Torres Strait Islander staff in service delivery and the integration of care across conditions and sectors [7]- [9]. Brach & Fraser [10], also suggest that culturally safe and competent services will translate into better health via the impact they have on improved communication, increased trust in the health system, greater knowledge about health and services in the local community and expanded cultural understanding within the health system.…”
Section: Introductionmentioning
confidence: 99%
“…54 Studies targeting different groups of health professionals have indicated that training in cultural competency has been beneficial for the health care of CALD communities. 55 Systematic rollout of education around CALD-specific issues has been limited. 56 Cultural knowledge/sensitivity and communication skills require ongoing training of research investigators through interactive courses, whether residential or online, with practical tips on making the best use of individual and institutional resources, enhancing cultural humility, and enabling culturally versed "global physicians."…”
Section: Improving Investigator Recruitmentmentioning
confidence: 99%